2019
DOI: 10.3390/molecules24030453
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C as a Modulator of the Response to Cancer Therapy

Abstract: Ascorbic acid (vitamin C) has been gaining attention as a potential treatment for human malignancies. Various experimental studies have shown the ability of pharmacological doses of vitamin C alone or in combinations with clinically used drugs to exert beneficial effects in various models of human cancers. Cytotoxicity of high doses of vitamin C in cancer cells appears to be related to excessive reactive oxygen species generation and the resulting suppression of the energy production via glycolysis. A hallmark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
69
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 77 publications
5
69
0
3
Order By: Relevance
“…This hypersensitivity to Asc has been linked to a heightened uptake of DHA by cancer cells due to their frequent overexpression of the DHA-transporting GLUT1, which is linked to specific oncogenic changes and the general increased dependency of transformed cells on aerobic glycolysis. Asc overloading and the resulting metabolic stress can also sensitize cancer cells to killing by some chemotherapeutic agents [17,34,53]. Our studies also found a stronger cytotoxicity of BLM in cells that were preincubated with DHA, however, this effect was unlikely linked to Asc overloading and the resulting metabolic/ energy stress.…”
Section: Discussionsupporting
confidence: 56%
“…This hypersensitivity to Asc has been linked to a heightened uptake of DHA by cancer cells due to their frequent overexpression of the DHA-transporting GLUT1, which is linked to specific oncogenic changes and the general increased dependency of transformed cells on aerobic glycolysis. Asc overloading and the resulting metabolic stress can also sensitize cancer cells to killing by some chemotherapeutic agents [17,34,53]. Our studies also found a stronger cytotoxicity of BLM in cells that were preincubated with DHA, however, this effect was unlikely linked to Asc overloading and the resulting metabolic/ energy stress.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, intravenously administered ascorbate also appears to affect DNA demethylation through the Tet2 enzyme, another Fe 2+ -2-oxoglutarate-dependent dioxygenase (7,47). Under homeostatic conditions, L-AA regulates the balance between self-renewal, differentiation, and cell death of hematopoietic stem cells and pluripotent progenitors by promoting Tet2 activity (4,10,47). Thus, L-AA may serve as an ROS modulator, a hypoxia stimulator, an epigenetic editor, and an enzyme cofactor during cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, L-AA inhibits the growth and metastasis of various types of cancers, including melanoma [14], breast cancer [15], gastric cancer [16], colorectal cancer [17], pancreatic cancer [18], and leukemia [19]. Many studies have reported that the L-AA concentration in the plasma of cancer patients (10~30 µM) is lower than that of healthy controls (50~100 µM) [20][21][22][23][24]. In adults, the recommended daily dose of L-AA is about 75-90 mg in USA [25], but administration of high-dose L-AA (8 g/day) is known to be effective in preventing common cold [26].…”
Section: Introductionmentioning
confidence: 99%